EKTRAKURIKULER SEBAGAI UPAYA PENGEMBANGAN BAKAT DAN MINAT PADA PESERTA DIDIK DI SDN CIHERANG 02 - Gulo, Trinatalis; Bellarmino, Edward; Wulandari, Lita Eka; Saputra, Arya Dwi; Budianto, Gabriel Arnold; Manik , Laura Bernadeth; Arisandi, Desi (Jurnal Serina Abdimas, 2024)
Extracurricular activities in Elementary Schools generally refer to activities or programs held outside of school hours that aim to develop students' talents, interests, skills, and character in various fields. These activities include various fields such as sports, arts, scouts, skills, and others, which are designed to provide a broader and deeper learning experience for students, as well as assist them in developing their personality and social skills, extracurricular programs play an important role in building students' character and abilities outside the academic curriculum. The development of talents and interests in extracurricular fields at SDN Ciherang 02 is still lacking in being implemented to students so that many still do not have extracurricular skills such as correct marching, correct singing, and exercising in accordance with applicable rules and so on. This is due to the lack of teaching staff who have special competence in these fields. Therefore, the Tarumanagara University Community Service Implementation Team implemented a Community Service Program to help solve the problems experienced by SDN Ciherang 02. Extracurricular programs at SDN Ciherang 02 include various activities, including sports, arts, and science, and are tailored to students' interests and talents. Through the development of extracurricular activities, it is expected that there will be development of social skills, leadership, and students' self-confidence through active participation in these activities. SDN Ciherang 2 is expected to continue to create a comprehensive learning environment and support each student according to their potential through extracurricular activities. ABSTRAK Kegiatan ekstrakurikuler di Sekolah Dasar secara umum merujuk pada kegiatan atau program yang diselenggarakan di luar jam pelajaran sekolah yang bertujuan untuk mengembangkan bakat, minat, keterampilan, serta karakter siswa di berbagai bidang. Kegiatan ini meliputi berbagai bidang seperti olahraga, seni, pramuka, keterampilan, dan lain-lain, yang dirancang untuk memberikan pengalaman belajar yang lebih luas dan mendalam bagi siswa, serta membantu mereka dalam pengembangan kepribadian dan kemampuan sosial, program ekstrakurikuler memainkan peran penting dalam membangun karakter dan kemampuan siswa di luar kurikulum akademik. Pengembangan bakat dan minat di bidang ekstrakurikuler di SDN Ciherang 02 masih kurang diimplementasikan kepada siwa/siswi sehingga masih banyak yang belum memiliki keterampilan ekstrakurikuler seperti baris berbaris yang benar, benyanyi yang benar, serta berolahraga yang sesuai dengan aturan yang berlaku dan lain sebagainya. Hail ini dikarenakan karena kurangnya tenaga pengajar yang memiliki kompetensi khusus dibidang tersebut. Maka dari itu Tim Pelaksana Abdimas Universitas Tarumanagara melaksanakan Program Pengabdian Kepada Masyarakat untuk membantu menyelesaikan permasalahan yang dialami oleh SDN Ciherang 02. Program ekstrakurikuler di SDN Ciherang 02 mencakup berbagai kegiatan, termasuk olahraga, seni, dan sains, dan disesuaikan dengan minat dan bakat siswa. Melalui pengembangan ekstrakurikuler diharapkan adanya perkembangan keterampilan sosial, kepemimpinan, dan kepercayaan diri siswa melalui partisipasi aktif dalam kegiatan ini. SDN Ciherang 2 diharapkan dapat terus menciptakan lingkungan belajar yang komprehensif dan mendukung setiap siswa sesuai dengan potensi siswa melalui kegiatan ekstrakurikuler